Integrasi Pendidikan Karakter dalam Pembelajaran Al-Quran - Muspirawati, Muspirawati; Amda, Ahmad Dibul; Saputra, Hasep (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to observe and analyze the integration of character education in learning the Qur'an and hadith at MTsN 1 Musi Rawas Utara. This type of research is field research, while the approach used is through a qualitative approach. The qualitative approach in this study is to match the empirical reality with the applicable theory by using a descriptive method. The results of the study obtained information that the integration of character education at MTsN 1 Musi Rawas Utara was carried out by planning, implementing, and assessing. In the search results, it can be seen that all character values ​​are integrated in the lesson plan for learning Al-Quran Hadith at MTsN 1 Musi Rawas Utara, then also integrated into the learning process of Al-Quran Hadith at MTsN 1 Musi Rawas Utara by the subject teacher. In conclusion, the integration of character education in learning the Qur'an and hadith for students at MTsN 1 Musi Rawas Utara has gone through planning, implementation and assessment, and has been integrated in the lesson plan and has been implemented by subject teachers. Keywords: Learning integration, Al-Quran Hadith Learning, Character Education.